Multilateral agreement on investments (MAI): A critical assessment from an industrial economics point of view - Andreas Polk (University of Zurich, Socioeconomic Institute, 2002)
Though the Multilateral Agreement on Investment (MAI) has failed, the original draft is likely to serve as a basis for future negotiations. This article gives a critical assessment of the draft from an industrial economics point of view. First, I summarize the contents of the agreement which is relevant for market structure and competition. Then I develop the industrial economics approach, which serves as a basis for criticism. I conclude that a multilateral agreement on investment should (i) recognize competition concerns, (ii) give a suitable de.nition of investment, and (iii) should help to establish competition authorities in less developed countries.
Keywords: D43; L43; 330; multilateral agreement on investment; multinational enterprizes; competition policy; regional competition; foreign direct investment; Direktinvestition; Internationales Abkommen; Industrieökonomik; Kritik; Welt